Analysis of in situ Transcriptomes Reveals Divergent Adaptive Response to Hyper- and Hypo-Salinity in the Hong Kong Oyster, Crassostrea hongkongensis - Xiao, Shu; Wong, Nai-Kei; Li, Jun; Lin, Yue; Zhang, Yuehuan; Ma, Haitao; Mo, Riguan; Zhang, Yang; Yu, Ziniu (Frontiers in Physiology, 2018)
Crassostrea hongkongensis, a commercially valuable aquaculture species dwelling in estuaries along the coast of the South China Sea, is remarkable for its eurysalinity traits that enable its successful colonization of diverse osmotic niches ranging from near freshwater to seawater. In order to elucidate how this oyster copes with coastal waters with immense salinity differences, we performed in situ transcriptomic analysis (RNA-seq) to characterize the global expression patterns of oysters distributed across naturally formed salinity gradients in Zhenhai Bay along the northern coast of the South China Sea. Principal component analysis reveals distinct expression profiles of oysters living in the extreme conditions of hypo-salinity and hyper-salinity. Compared with the situation of optimal salinity for oyster growth, hypo-salinity mainly regulated expression of genes involved in FoxO and oxytocin signaling, tight junction and several immune pathways, while hyper-salinity altered gene expression implicated in amino acid metabolism, AMPK and PI3K-AKt signaling pathways, demonstrating the complexity and plasticity of transcriptomic expression underpinning oyster eurysalinity. Furthermore, the expression patterns of several genes correlated with salinity gradients reveals the fine-tuned coordination of molecular networks necessary for adaptive homeostasis in C. hongkongensis. In conclusion, a striking capacity and distinct patterns of transcriptomic expression contribute to eurysalinity adaptation in C. hongkongensis, which provides new mechanistic insights into the adaptive plasticity and resilience of marine mollusks.